Lobectomy versus sublobar resection for stage I (T1‐T2aN0M0) small cell lung cancer: A SEER population‐based propensity score matching analysis. (25th December 2022) - Zhou, Ning; Yang, Lingqi; Zhang, Bo; Zhu, Shuai; Huo, Huandong; He, Jinling; Zu, Lingling; Song, Zuoqing; Xu, Song
Abstract: Objective: This study evaluated whether sublobar resection (sub‐L) is non‐inferior to lobectomy (L) for stage I (T1‐T2aN0M0) small cell lung cancer (SCLC) regarding long‐term overall survival (OS). Methods: Clinicopathological and prognostic data of patients with stage I (pT1‐T2aN0M0) SCLC were retrieved. Kaplan–Meier curves and Breslow tests were performed for the assessment of OS. Propensity score matching (PSM) analysis was used to mediate the inherent bias of retrospective researches. Results: A total of 188 patients with stage I SCLC were included in this study after PSM. For resected stage I SCLC, surgery plus adjuvant therapy was related to a better OS compared with surgery only ( p  = 0.016). For resected stage I SCLC, no matter adjuvant therapy was performed or not, no significant difference was observed in long‐term OS between the L and sub‐L groups ( p  = 0.181). Further subgroup analysis demonstrated that the OS disadvantage of sub‐L over L was not statistically significant for stage I SCLC patients underwent surgery only ( p  = 0.653), but also for the patients underwent surgery plus adjuvant therapy ( p  = 0.069). Moreover, in the subgroup analyses according to TNM stage (IA and IB), sex (male and female), and age (≥70 and <70 years), OS did not differ between the L and sub‐L groups except in female patients ( p  = 0.008). Multivariate Cox regression analysis indicated that adjuvant therapy was positively associated with OS. Conclusions: Surgery plus adjuvant therapy confers a better survival benefit than surgery only for stage I SCLC patients. However, as far as the range of surgical resection is concerned, sublobar resection may be non‐inferior to lobectomy regarding OS. Our study could conduce to the development of optimal therapeutic strategies for stage I SCLC patients. Further validation is warranted in larger retrospective and prospective cohort studies. Abstract : This study evaluated the non‐inferior role of sublobar resection to lobectomy for stage I (T1‐2aN0M0) SCLC. We found that lobectomy was superior to sublobar resection in OS (A) and LCSS (C) before PSM, but no significant difference was observed between sublobar resection and lobectomy in OS (B) and LCSS (D) after PSM.